El V Pleno Jurisdiccional Supremo Laboral y las innovaciones en los casos de despido incausado y fraudulento - Liza Castillo, Luis Manuel (2021)
The purpose of this research work is to analyze and describe the scope of the V Plenary Supreme Labor and Social Security Jurisdiction, particularly the treatment of compensation and remuneration accrued in unjustified and fraudulent dismissals. In this context, the importance of labor stability (absolute in the 1979 Constitution and relative in the 1993 Constitution) should be emphasized. The «Huatuco Huatuco» precedent establishes bases that only consolidate relative labor stability; and limits, in some way, the right of workers, since many of them did not enter through public competition, a fact that creates legal defenselessness against arbitrary dismissal. It also affects other workers’ rights, such as the payment of accrued remuneration. This situation has not been duly addressed by the plenary, which leads to the formation of a current of opinion regarding the criterion adopted.